Childhood, adolescent, and young adulthood cancer risk in BRCA1 or BRCA2 pathogenic variant carriers - Li, Shuai; Madanat-Harjuoja, Laura; Leslie, Goska; Barnes, Daniel R; Bolla, Manjeet K; Dennis, Joe; Parsons, Michael T; Apostolou, Paraskevi; Arnold, Norbert; Bosse, Kristin; Cook, Jackie; Engel, Christoph; et al. (Journal of the National Cancer Institute, 2024)
Whether carriers of BRCA1 or BRCA2 pathogenic variants have increased risks of childhood, adolescent, and young adult cancers is controversial. We aimed to evaluate this risk and to inform clinical care of young BRCA1 and BRCA2 pathogenic variant carriers and genetic testing for childhood, adolescent, and young adult cancer patients.Using data from 47117 individuals from 3086 BRCA1 or BRCA2 families, we conducted pedigree analysis to estimate relative risks (RRs) for cancers diagnosed before age 30 years.Our data included 274 cancers diagnosed before age 30 years: 139 breast cancers, 10 ovarian cancers, and 125 nonbreast nonovarian cancers. Associations for breast cancer in young adulthood (aged 20-29 years) were found with relative risks of 11.4 (95% confidence interval [CI] = 5.5 to 23.7) and 5.2 (95% CI = 1.6 to 17.7) for BRCA1 and BRCA2 pathogenic variant carriers, respectively. No association was found for any other investigated childhood, adolescent, and young adult cancer or for all nonbreast nonovarian cancers combined; the relative risks were 0.4 (95% CI = 0.1 to 1.4) and 1.4 (95% CI = 0.7 to 3.0) in BRCA1 and BRCA2 pathogenic variant carriers, respectively.We found no evidence that BRCA1 and BRCA2 pathogenic variant carriers have an increased childhood, adolescent, and young adult cancer risk aside from breast cancer in women aged between 20 and 30 years. Our results, along with a critical evaluation of previous germline sequencing studies, suggest that the childhood and adolescent cancer risk conferred by BRCA1 and BRCA2 pathogenic variant would be low (ie, RR < 2) if it existed. Our findings do not support pathogenic variant testing for offspring of BRCA1 and BRCA2 pathogenic variant carriers at ages younger than 18 years or for conducting BRCA1 and BRCA2 pathogenic variant testing for childhood and adolescent cancer patients.
Gesehen am 06.10.2025